2015
DOI: 10.1155/2015/405036
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Phenol from Aqueous Solutions by Carbon Nanomaterials of One and Two Dimensions: Kinetic and Equilibrium Studies

Abstract: Carbon nanomaterials have a great potential in environmental studies; they are considered as superior adsorbents of pollutants due to their physical and chemical properties. Functionalization and dimension play an important role in many functions of these nanomaterials including adsorption. In this research, adsorption process was achieved with one-dimension nanomaterials: single walled and multiwalled carbon nanotubes were used as received and after oxidation treatment also two-dimensional nanomaterials were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 57 publications
0
33
0
3
Order By: Relevance
“…The reason is that the pore sizes of mesopores formed by Fe 2 O 3 particles enlarge the size distribution of CNTs. The curves indicate that mesopores with pore sizes between 3 and 5 nm present a wide distribution in supports and catalysts . Besides, the mesoporous and macroporous pore diameter distributions of the MF‐CNT supports and Fe 2 O 3 ‐MF‐CNT catalysts were tested by mercury porosimetry and the results were shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is that the pore sizes of mesopores formed by Fe 2 O 3 particles enlarge the size distribution of CNTs. The curves indicate that mesopores with pore sizes between 3 and 5 nm present a wide distribution in supports and catalysts . Besides, the mesoporous and macroporous pore diameter distributions of the MF‐CNT supports and Fe 2 O 3 ‐MF‐CNT catalysts were tested by mercury porosimetry and the results were shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The curves indicate that mesopores with pore sizes between 3 and 5 nm present a wide distribution in supports and catalysts. 39 Besides, the mesoporous and macroporous pore diameter distributions of the MF-CNT supports and Fe 2 O 3 -MF-CNT catalysts were tested by mercury porosimetry and the results were shown in Figure 4. As can be seen, no pore size was observed between 20 and 100 nm for both samples, and the pore sizes of the macropores in the sample are about 6000-7000 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Equilibrium studies on the adsorption process are important in order to provide information on the adsorbent capacity or amount required to remove a unit mass of pollutant [26][27][28]. An adsorption isotherm indicates the surface properties of an adsorbent or to adsorption capacity towards certain pollutant which usually express by certain constant depends on the model being used.…”
Section: Adsorption Isotherm and Kinetic Studymentioning
confidence: 99%
“…dioxin [3]) that constitute negative impacts on public health and the environment alike. As a solution, adsorption processes stand out in providing a viable clean-up treatment for this matter due to their relatively simple implementation [4]. Moreover in theory, ultrathin nanomaterials, such as graphene, exhibit remarkable properties to assist the adsorption procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In relations to phenol-graphene interaction, phenolic materials have been used to adsorb epoxy (O) or hydroxyl (OH) in graphene oxide to synthesize graphene [18,19]. For the reverse process, Luz et al reported from their experiment that, phenol adsorbed weakly on graphene in a graphite-like interaction [4]. An experiment by Huang et al suggested the application of defective oxygenated graphene to attract water molecules for humidity sensor [20].…”
Section: Introductionmentioning
confidence: 99%